Harnessing Bifunctional Ferritin with Kartogenin Loading for Mesenchymal Stem Cell Capture and Enhancing Chondrogenesis in Cartilage Regeneration. Issue 8 (17th January 2022) - Ren, En; Chen, Haimin; Qin, Zainen; Guan, Siwen; Jiang, Lai; Pang, Xin; He, Yi; Zhang, Yang; Gao, Xing; Chu, Chengchao; Zheng, Li; Liu, Gang
Abstract: Methods that leverage bone marrow mesenchymal stem cells (BMSCs) and stimulating factor kartogenin (KGN) for chondrocyte differentiation have paved the way for cartilage repair. However, the scarce carriers for efficiently bridging the two components significantly impede their further application. Therefore, one kind of bifunctional ferritin has designed and synthesized: RC‐Fn, a genetically engineered ferritin nanocage with RGD peptide and WYRGRL peptide on the surface. The RGD can target the integrin α v β 3 of BMSCs and promote proliferation, and the WYRGRL peptide has an inherent affinity for the cartilage matrix component of collagen II protein. RC‐Fn nanocages have an ideal size for penetrating the proteoglycan network of cartilage. Thus, intra‐articularly injected RC‐Fn with KGN loading can convert the articular cavity from a barrier into a reservoir to prevent rapid release and clearance of KGN and exogenous BMSCs, which results in efficient and persistent chondrogenesis in cartilage regeneration. Abstract : Bifunctional ferritin RC‐Fn nanocage is genetically engineered with RGD peptide and WYRGRL peptide on the surface and loaded with stimulating factor kartogenin for mesenchymal stem cell capture and enhancing chondrogenesis in cartilage regeneration.